2022
DOI: 10.3390/insects13060502
|View full text |Cite
|
Sign up to set email alerts
|

Soldier Caste-Specific Protein 1 Is Involved in Soldier Differentiation in Termite Reticulitermes aculabialis

Abstract: Termite soldiers are a unique caste among social insects, and their differentiation can be induced by Juvenile hormone (JH) from workers through two molts (worker–presoldier–soldier). However, the molecular mechanism underlying the worker-to-soldier transformation in termites is poorly understood. To explore the mechanism of soldier differentiation induced by JH, the gene soldier caste-specific protein 1 (RaSsp1, NCBI accession no: MT861054.1) in R. aculabialis was cloned, and its function was studied. This ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The takeout gene reported in R. aculabialis ( RaSsp1 ), which is most closely related to RsTO2 (Supplementary Figure S2 ), may bind to JH III and is involved in the regulation of soldier differentiation 20 . To clarify whether RsTO2 interacts with JH III before molts and is involved in soldier differentiation, functional analysis should be performed during presoldier and soldier differentiation under natural conditions without hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The takeout gene reported in R. aculabialis ( RaSsp1 ), which is most closely related to RsTO2 (Supplementary Figure S2 ), may bind to JH III and is involved in the regulation of soldier differentiation 20 . To clarify whether RsTO2 interacts with JH III before molts and is involved in soldier differentiation, functional analysis should be performed during presoldier and soldier differentiation under natural conditions without hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that takeout (named Deviate ) elicited trail-following behavior in R. flavipes 19 . In R. aculabialis , takeout (named RaSsp1 ) was highly expressed in soldiers and was suggested to interact with JH III and participate in soldier differentiation 20 . In the termitid termite Nasutitermes takasagoensis , takeout (named Ntsp1 ) is highly expressed in the soldier frontal gland and probably combines with gland secretions 21 .…”
Section: Introductionmentioning
confidence: 99%
“…To analysis the effect of JH on the soldier's defensive behaviors, there was minor treatment changes in JHA (Pyriproxyfen, Sigma, Steinheim, Germany) fed to the termites. According to the previous reports, the purity of pyriproxyfen is 99% [17]. The induction rate of 120 µg pyriproxyfen-treated soldiers is like that of 200 ug, but the mortality rate is quite different [27].…”
Section: Insect Collection and Jh Treatmentmentioning
confidence: 99%
“…As one of the most phenotypically plastic insects, the soldier caste fate in termites could be changed during postembryonic development. That is, a constant high juvenile hormone (JH), or the juvenile hormone analogue pyriproxyfen (JHA), titer triggers soldier differentiation from workers through two molting periods via a pre-soldier stage (that is, worker-pre-soldier-soldier) [4,17]. During this differentiation process, the allometry of soldier's head occurs, especially regarding the exaggeratedly enlarged mandibles, which are special weapons of soldiers' defense [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation